Delta hepatitis-related thyroid disease: a unique phenomenon - Suvak, Burak; Dulger, Ahmet Cumhur; Aykaç, Mehmet Coskun; Gonullu, Hayriye; Gonullu, Edip (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Introduction : Hepatitis delta virus (HDV) infection is a serious health problem worldwide. Thyroid disturbances represent a major limitation to the efficacy of interferon treatment targeting chronic HDV (C-HDV) infection. Moreover, pre-treatment thyroid diseases may be influenced by interferon therapy. Despite this, the characteristic features of the thyroid diseases in C-HDV patients remain poorly characterised. Aim: To determine the prevalence of thyroid diseases and evaluate the impact of delta hepatitis on thyroid function tests. Material and methods : We retrospectively reviewed the charts of 127 hepatitis C virus (HCV)-negative adults, treatment-naive outpatients with C-HDV, between July 2013 and July 2014. Thyroid-stimulating hormone (TSH) and thyroid antibodies (TAbs) including anti-thyroid peroxidase antibodies (anti-TPO), liver transaminases, and other routine laboratory tests were conducted during the study period. Results : A total of 127 C-HDV patients (female 52.9%, mean age 54.5 ±8.01 years) were enrolled. The rate of hypothyroidism, defined as a TSH level above 10 IU/l, was 4.7%. No patient had hyperthyroidism. Both elevated levels of liver transaminases and HDV ribonucleic acid (HDV-RNA) were positively correlated with high levels of thyroid autoantibodies. Conclusions : The rate of hypothyroidism is higher than the rate of hyperthyroidism at baseline. Most remarkably, for the first time we discovered a correlation between disturbed thyroid autoantibodies and elevated liver transaminases as well as high HDV-RNA levels even in euthyroid delta hepatitis patients. But in order to have an adequate understanding of such correlations, further studies are needed.